Use of Onyx for Transarterial Balloon-Assisted Embolization of Traumatic Carotid Cavernous Fistulas: A Report of 23 Cases - Yu, Y.; Huang, Q.; Xu, Y.; Hong, B.; Zhao, W.; Deng, B.; Zhang, Y.; Liu, J. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: TCCFs are a common complication following craniofacial trauma and are usually treated by coils or detachable balloons. The use of the liquid embolic agent Onyx as the sole agent for the treatment of TCCFs has been rarely reported. Herein, we summarized the preliminary experience and effectiveness of treating TCCFs with Onyx in 23 patients. MATERIALS AND METHODS: From the 36 type A CCFs treated in our department between September 2005 and March 2011, a total of 23 posttraumatic direct CCFs were treated by using Onyx only via transarterial approach. RESULTS: Immediate postprocedural angiograms demonstrated complete occlusion in all patients. All the patients underwent a single procedure except 1 with bilateral TCCFs. Up to 24-month clinical and 3-month angiographic follow-ups revealed an ongoing complete occlusion without any complications. CONCLUSIONS: In this series, the use of Onyx for the transarterial embolization of TCCFs was feasible and effective. Associated adverse events were rare. CCFcarotid cavernous fistulaCScavernous sinusDAVFdural arteriovenous fistulaDMSOdimethyl-sulfoxidenBCAn-butyl 2-cyanoacrylateTCCFtraumatic carotid cavernous fistula